2020
DOI: 10.1186/s12887-020-02329-w
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D supplementation in obese Sri Lankan children: a randomized controlled trial

Abstract: Background: Micronutrient deficiencies are identified among obese individuals. Vitamin D deficiency (VDD) is prevalent in obese children, and is hypothesized to cause insulin resistance and metabolic abnormalities. This study aimed to determine the effect of vitamin D supplementation on obesity and related metabolic abnormalities among obese Sri Lankan children with VDD. Methods: A triple-blind randomized controlled trial was conducted among vitamin D deficient (< 20 ng/ml), obese children (n = 96), randomly a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…Also, obese individuals have been noted to have vitamin D deficiency. Vitamin D is an essential nutrient that plays an important role in calcium homeostasis [55]. In a paediatric population, an association between low vitamin D level and activation of pro-inflammatory pathways among the obese has been identified [56].…”
Section: Discussionmentioning
confidence: 99%
“…Also, obese individuals have been noted to have vitamin D deficiency. Vitamin D is an essential nutrient that plays an important role in calcium homeostasis [55]. In a paediatric population, an association between low vitamin D level and activation of pro-inflammatory pathways among the obese has been identified [56].…”
Section: Discussionmentioning
confidence: 99%
“…The overall RoB for all the six RCTs on hypercalcaemia among children and adolescents was considered moderate (Tier 2) (Asghari et al 2021;Belenchia et al 2013;Lewis et al 2013;Maalouf et al 2008;Rajakumar et al 2020;Samaranayake et al 2020) (Table 5). All three key domains raised concern regarding RoB;…”
Section: Hypercalcaemia Among Children and Adolescentsmentioning
confidence: 99%
“…Four RCTs included only overweight or obese children (Asghari et al 2021;Belenchia et al 2013;Rajakumar et al 2020;Samaranayake et al 2020), while BMI status was unclear in two RCTs (Lewis et al 2013;Maalouf et al 2008). The mean baseline S-25(OH)D concentrations were between 25 to 49 nmol/L in five RCTs (Asghari et al 2021;Belenchia et al 2013;Maalouf et al 2008;Rajakumar et al 2020;Samaranayake et al 2020) and between 50 to 74 nmol/L in one RCT (Lewis et al 2013).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although weight loss is associated with increased circulating 25(OH)D levels (69, 70), the reciprocal beneficial effect of vitamin D status on body fat mass remains controversial among clinical studies. Some clinical trials have reported that native vitamin D supplementation favorizes weight loss, body fat mass reduction and metabolic profile in obese adult (154) and pediatric (155,156) population, while in other studies no related difference on weight loss was observed in obese subjects assigned to receive daily native vitamin D (157). Therefore, the effect of native vitamin D supplementation on successfully body fat mass reduction remains unclear, with a total insignificant effect reported by some (158,159) but not all meta-analysis studies (160).…”
Section: Impact Of Mineral Homeostasis On Fat Mass and Adipokine Profile In General Populationmentioning
confidence: 99%